A phosphorus-doped lithium-rich manganese-based hydroxide precursor and a preparation method thereof
Patent Information
- Application Number
- CN202611221824.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
然而,现有的制备技术在实际应用中仍存在明显的局限性:首先,部分工艺受限于碳酸盐前驱体的本征特性,沉淀反应易不完全,且在后续烧结过程中前驱体分解产气量大,造成材料比表面积过大
[0017]此外,均匀分布于前驱体体相中的磷酸根在后续的高温烧结配锂过程中,能够与表面的残余锂盐发生反应,原位衍生出无定形磷酸锂包覆层。该界面层结构不仅能够消耗界面处的游离酸性副产物,有效抑制金属离子溶出导致的结构坍塌,还能有效降低电荷转移电阻并促进锂离子的快速传输。这在大幅增强材料界面稳定性的同时,有效缓解了富锂锰基材料在长期充放电循环过程中的电压衰减现象,提升了最终产品的综合电化学储能表现。
Smart Images

Figure CN123002804A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and more specifically, to a phosphorus-doped lithium-rich manganese-based hydroxide precursor and its preparation method. Background Technology
[0002] Lithium-rich manganese-based materials have become an important research direction for next-generation high-performance cathode materials due to their high specific capacity. The physicochemical properties and microstructure of the precursor have a decisive influence on the structure and electrochemical performance of the final cathode material. Therefore, morphology control and structural modification of the precursor through co-precipitation processes have always been a conventional technique in this field.
[0003] In existing precursor synthesis processes, heterogeneous element doping is often introduced to improve material properties. For example, fluorine is introduced during synthesis to induce the nucleation and growth of the precursor. However, existing preparation techniques still have significant limitations in practical applications: First, some processes are limited by the intrinsic characteristics of carbonate precursors, resulting in incomplete precipitation reactions and large gas production from precursor decomposition during subsequent sintering, leading to an excessively large specific surface area of the material. The resulting electrodes often have low compaction density due to loose particle packing, directly limiting the energy density of the battery. Second, to improve morphology, existing technologies often introduce elements such as fluorine (F) for doping, but this greatly increases the difficulty of wastewater treatment, leading to a significant increase in environmental costs. Simultaneously, in existing doping co-precipitation processes, the lack of precise matching between the flow field and reaction atmosphere during the dynamic growth stage of precursor particles makes it difficult to prepare precursors with both excellent microstructure and high density while avoiding environmental pollution.
[0004] In summary, obtaining a precursor that can avoid the environmental problems associated with fluorine-containing materials and optimize particle micromorphology through structural modification and growth process control, thereby improving the final material density and compaction density, is a technical bottleneck that urgently needs to be overcome in this field.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a phosphorus-doped lithium-rich manganese-based hydroxide precursor and its preparation method. This invention utilizes the lattice phase doping of phosphate to induce dense growth of micro-particles to improve tap density, and in situ generates an interface coating layer during the sintering stage, which effectively alleviates the voltage decay of lithium-rich materials.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, a phosphorus-doped lithium-rich manganese-based hydroxide precursor, wherein the chemical formula of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is Ni a Mn b(OH) 2-3x (PO4) x ; where 0.4≤a≤0.6, 0.4≤b≤0.6, a+b=1, 0.0001<x≤0.0015; In the phosphorus-doped lithium-rich manganese-based hydroxide precursor, phosphorus element is doped in the crystal lattice of the precursor in the form of phosphate ions, and replaces part of hydroxide ions.
[0008] In an optional embodiment, x satisfies 0.0003<x≤0.0015; and / or, The mass fraction of phosphorus element in the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 100ppm~500ppm; and / or, The specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 22m 2 / g~45m 2 / g; preferably, the specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 28m 2 / g~41m 2 / g; and / or, The tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.0g / cm 3 ~2.2g / cm 3 ; preferably, the tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.5g / cm 3 ~1.9g / cm 3 .
[0009] In an optional embodiment, the precursor is spherical or quasi-spherical secondary particles formed by agglomeration of primary particles; Preferably, the primary particles are acicular or flaky; Preferably, the thickness of the primary particles is 50nm~150nm; Preferably, the length of the primary particles is 130nm~500nm; Preferably, the aspect ratio of the primary particles is ≥2; Preferably, the particle size D50 of the secondary particles is 7μm~11μm; more preferably, the particle size D50 of the secondary particles is 7.5μm~10μm; and / or, Preferably, the particle size distribution width Span of the secondary particles is 0.55~0.9; more preferably, the particle size distribution width Span of the secondary particles is 0.60~0.70.
[0010] In a second aspect, the present invention further provides a method for preparing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in the foregoing embodiments, comprising: A co-precipitation reaction is carried out by simultaneously and in parallel injecting a mixed salt solution containing nickel and manganese metal salts, an alkaline solution, and a phosphorus source solution into a reaction vessel containing a base liquid; wherein the solute in the phosphorus source solution is sodium phosphate dodecahydrate. During the coprecipitation reaction, gas is introduced into the reaction vessel, and as the reaction proceeds, the feed flow rates of the mixed salt solution and the phosphorus source solution, the stirring speed in the reaction vessel, and the gas flow rate are adjusted to obtain the reaction product. The reaction product was subjected to solid-liquid separation, washing, and drying to obtain the phosphorus-doped lithium-rich manganese-based hydroxide precursor.
[0011] In an optional embodiment, the step of introducing gas into the reaction vessel specifically includes: increasing the gas flow rate as the reaction time increases during the co-precipitation reaction; and / or, The stirring speed within the reaction vessel is decreased as the particle size of the precursor in the reaction system increases; and / or, Prior to the coprecipitation reaction, the process includes a step of preparing the base solution: injecting a mixed salt solution containing nickel and manganese metal salts, along with an alkaline solution, into a reaction vessel to carry out nucleation and growth reactions; after separation to obtain seed crystals, mixing the seed crystals with water to obtain the base solution; and / or, During the coprecipitation reaction, the pH of the reaction system in the reaction vessel is controlled at 9.00~9.60.
[0012] In an optional embodiment, the stirring speed within the reaction vessel is reduced as the particle size of the precursor in the reaction system increases, including: First stage: Simultaneously inject the mixed salt solution, the alkaline solution, and the phosphorus source solution at the initial flow rate, and adjust the flow rate of the alkaline solution to control the pH of the reaction system to be maintained between 9.00 and 9.20; Second stage: Increase the feed flow rate of the mixed salt solution and the phosphorus source solution to 1.8 to 2.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.20 and 9.40; when the particle size D50 of the precursor in the system reaches 30% to 35% of the target total particle size, reduce the linear velocity of the stirring speed to 7.0 to 7.5 m / s; Third stage: Increase the feed flow rate to 2.8 to 3.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.40 and 9.60; when the particle size D50 of the precursor in the system reaches 48% to 55% of the target total particle size, reduce the linear velocity of the stirring speed to 6.0 m / s to 6.5 m / s. Fourth stage: Increase the feed flow rate to 3.8 to 4.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.20 and 9.40; when the particle size D50 of the precursor in the system reaches 60% to 68% of the target total particle size, reduce the linear velocity of the stirring speed to 5.0 to 5.5 m / s.
[0013] In an optional embodiment, during the coprecipitation reaction, as the reaction time increases, the gas flow rate is increased, including: After injecting the mixed salt solution, the alkaline solution, and the phosphorus source solution for 2.5 to 3.5 hours, gas is introduced into the reaction vessel at an initial flow rate. Thereafter, the gas flow rate is increased every 2.5 to 3.5 hours until a preset maximum flow rate threshold is reached. Preferably, the initial flow rate is 0.05 L / hour to 0.15 L / hour; preferably, the increase in gas flow rate each time is 0.15 L / hour to 0.25 L / hour; preferably, the preset maximum flow rate threshold is 1.8 L / hour to 2.0 L / hour; and / or, The gas introduced into the reaction vessel is air, oxygen, or a mixture of oxygen and an inert gas; and / or, The preparation step of the base liquid further includes: introducing air, oxygen, or a mixture of oxygen and an inert gas into the reaction vessel.
[0014] Thirdly, the present invention provides a lithium-rich manganese-based cathode material, which is prepared by mixing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in the foregoing embodiments, or by using the phosphorus-doped lithium-rich manganese-based hydroxide precursor prepared by the method described in the foregoing embodiments, and then sintering it with a lithium source. Preferably, the surface of the lithium-rich manganese-based cathode material has an in-situ derived amorphous Li3PO4 coating layer.
[0015] Fourthly, the present invention provides a lithium-ion battery, including a positive electrode, wherein the active material of the positive electrode includes the lithium-rich manganese-based positive electrode material as described in the foregoing embodiments.
[0016] Compared with existing technologies, the precursor provided by this invention effectively maintains the overall charge balance of the crystal by introducing phosphate groups into the crystal lattice for bulk doping and precisely replacing some hydroxide ions, thus avoiding the lattice distortion and cation mixing defects easily caused by conventional metal cation doping. The introduced phosphate groups, as heterogeneous anions, can significantly change the crystal plane energy, thereby weakening the tendency of precursor particles to grow along the a-axis and inducing their dominant growth along the c-axis. This regulation of crystal plane growth orientation effectively suppresses the excessive growth of primary particles, promoting the refinement of primary particle size and a more consistent arrangement orientation, thereby constructing a dense microstructure of secondary particles. This microstructure can significantly reduce the free specific surface area of the material and increase the overall tap density, laying a solid material foundation for improving the subsequent battery electrode tap density and energy density.
[0017] Furthermore, the phosphate ions uniformly distributed in the bulk phase of the precursor can react with residual lithium salts on the surface during subsequent high-temperature sintering and lithium formulation, generating an amorphous lithium phosphate coating layer in situ. This interfacial layer structure not only consumes free acidic byproducts at the interface, effectively suppressing structural collapse caused by metal ion dissolution, but also effectively reduces charge transfer resistance and promotes rapid lithium ion transport. This significantly enhances the interfacial stability of the material while effectively mitigating voltage decay during long-term charge-discharge cycles of lithium-rich manganese-based materials, thus improving the overall electrochemical energy storage performance of the final product. Attached Figure Description
[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0019] Figure 1 This is a SEM image of the phosphorus-doped lithium-rich manganese-based hydroxide precursor provided in Example 1 of the present invention; Figure 2 This is a cross-sectional SEM image of the phosphorus-doped lithium-rich manganese-based hydroxide precursor provided in Example 1 of the present invention; Figure 3 This is a cross-sectional EDS surface scan of phosphorus element in the phosphorus-doped lithium-rich manganese-based hydroxide precursor provided in Example 1 of the present invention. Figure 4 This is a SEM image of the lithium-rich manganese-based hydroxide precursor provided in Comparative Example 1 of the present invention. Figure 5 The XRD patterns (A) of the cathode materials prepared in Example 1 and Comparative Example 1 of the present invention and the enlarged view (B) of the (003) crystal plane diffraction peaks are shown. Figure 6 This is a microstructure diagram of the precursor when phosphorus is excessively doped (1200 ppm) in the embodiments of this application. Detailed Implementation
[0020] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0021] This application provides a phosphorus-doped lithium-rich manganese-based hydroxide precursor, the precursor having the chemical formula Ni. a Mn b (OH) 2-3x (PO4) x .
[0022] Where 0.4 ≤ a ≤ 0.6 (e.g., 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, etc.), 0.4 ≤ b ≤ 0.6 (e.g., 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, etc.), a + b = 1, 0.0001 < x ≤ 0.0015 (e.g., 0.0001, 0.0003, 0.0005, 0.0008, 0.0010, 0.0012, 0.0015, etc.). In the precursor, phosphorus is doped into the precursor lattice in the form of phosphate ions and replaces some hydroxide ions.
[0023] In this embodiment of the invention, phosphorus is not simply attached to the particle surface in the form of elemental, metal ion, or oxide, but rather uniformly enters the bulk lattice of the precursor as phosphate anions. Through the mechanism of one phosphate ion precisely replacing three hydroxide ions, the overall charge balance within the crystal is maintained, and the lattice distortion problem easily caused by conventional cation substitution doping is largely avoided. Furthermore, the introduced phosphate ion, as a heterogeneous ion, alters the crystal plane energy of the precursor, weakening the thermodynamic tendency of particle growth along the a-axis and instead inducing dominant growth along the c-axis, thus suppressing excessive growth of primary particles. Ultimately, the growth orientation of the primary particles tends to be uniform, constructing a microstructure with fine particle size and dense secondary particle packing. This densified structure effectively reduces the free specific surface area and significantly increases the tap density, thereby improving the compaction density during subsequent electrode fabrication and contributing to the overall energy density of the lithium-ion battery.
[0024] In summary, the precursor provided in this embodiment achieves bulk doping by replacing part of the hydroxide radicals in the crystal lattice with phosphate radicals, which not only avoids lattice distortion, but also induces the preferential growth of particles along the c-axis and refines primary particles by changing the crystal plane energy. This makes the secondary particles pack more densely, effectively reduces the specific surface area and significantly increases the tap density, which is beneficial to improving the compaction density of the final electrode plate. At the same time, the bulk-doped phosphate radicals can in-situ derive an amorphous coating layer with residual lithium salts in the subsequent sintering process, which can greatly enhance the interfacial stability of the material, thereby effectively alleviating the voltage attenuation problem of lithium-rich manganese-based cathode materials during cycling.
[0025] In some embodiments, the variable x satisfies 0.0003<x≤0.0015. For example, it can be 0.0003, 0.0005, 0.0008, 0.0010, 0.0012, 0.0015 and so on.
[0026] In some embodiments, the mass fraction of phosphorus element in the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 100ppm to 500ppm; preferably, the mass fraction of phosphorus element in the precursor is selected from 100ppm, 350ppm or 500ppm.
[0027] In the embodiments of the present invention, precisely controlling the doping amount of phosphorus element inside the crystal lattice is the key to realizing the synergistic optimization of the precursor's microstructure and macroscopic powder properties. Appropriate bulk doping of phosphate radicals can effectively change the crystal plane energy, induce the primary particles of the precursor to grow preferentially along the c-axis and refine the particle size.
[0028] However, when the doping amount of phosphorus element is too low (for example, lower than 100ppm), the regulation effect of phosphate radicals on the crystal plane energy is weak, and the microscopic morphology and macroscopic powder properties of the precursor are similar to those of the undoped system, which cannot effectively exert the modification effect of inducing the preferential growth and refinement of particles. On the contrary, when the doping amount of phosphorus element is too high (for example, exceeding 500ppm), an over-doping effect will occur in the precursor system, which will lead to abnormal coarsening of the primary particles and a significant increase in the aspect ratio. Sintering will cause the microstructure to densify, which is not conducive to the transport and diffusion of lithium ions.
[0029] Therefore, the present invention controls the mass fraction of phosphorus element in the precursor between 100ppm and 500ppm. Within this range, the growth orientation of the primary particles tends to be highly consistent, forming a microstructure with fine particle size and dense packing of secondary particles.
[0030] In some embodiments, the specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 22m 2 / g~45m 2 / g; for example, it can be 22m 2 / g, 25m 2 / g、28m 2 / g、30m 2 / g、32m 2 / g、35m 2 / g、38m 2 / g、40m 2 / g、41m 2 / g、45m 2 / g etc. Preferably, the specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 28m². 2 / g~41m 2 / g. For example, it can be 28m. 2 / g、29m 2 / g、30m 2 / g、32m 2 / g、35m 2 / g、36m 2 / g、38m 2 / g、39m 2 / g、40m 2 / g、41m 2 / g etc. The moderate specific surface area effectively avoids the problem of excessive precursor decomposition rate during sintering and reduces local side reactions between the cathode material and the electrolyte.
[0031] In some embodiments, the tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.0 g / cm³. 3 ~2.2g / cm 3 For example, it could be 1.0 g / cm³. 3 1.2g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.7g / cm 3 1.8g / cm 3 1.9g / cm 3 2.0g / cm 3 2.2g / cm 3 Etc. Preferably, the tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.5 g / cm³. 3 ~1.9g / cm 3 For example, it could be 1.50 g / cm³. 3 1.55g / cm 3 1.60g / cm 3 1.63g / cm 3 1.68g / cm 3 1.72g / cm 3 1.75g / cm3 1.80g / cm 3 1.85g / cm 3 1.90g / cm 3 And so on. This significant improvement in tap density overcomes the defect of low tap density in lithium-rich manganese-based electrode materials from the source, providing a material basis for improving the volumetric energy density of the final lithium-ion battery.
[0032] In some embodiments, the precursor is a spherical or near-spherical secondary particle formed by the aggregation of primary particles. The multi-level morphology of the precursor has a significant impact on the processing performance and electrochemical performance of the final cathode material. By introducing phosphate ions for lattice phase doping during the co-precipitation reaction stage, the presence of heterogeneous phosphate ions alters the surface energy of the crystal surface, effectively weakening the growth tendency of the precursor along the a-axis (high atomic density direction) and inducing its dominant growth along the c-axis.
[0033] Furthermore, the primary particles are needle-shaped or flake-shaped.
[0034] Furthermore, the thickness of the primary particles is 50nm~150nm; for example, it can be 50nm, 60nm, 75nm, 80nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, etc.
[0035] Furthermore, the length of the primary particle is 130nm~500nm; for example, it can be 130nm, 150nm, 180nm, 220nm, 280nm, 330nm, 380nm, 420nm, 460nm, 500nm, etc.
[0036] Furthermore, the aspect ratio of the primary particles is ≥2.
[0037] Specifically, the thickness of the primary particles is controlled within the range of 50nm to 150nm, the length is controlled within the range of 130nm to 500nm, and the aspect ratio is ≥2. These refined primary particles with a certain aspect ratio tend to have a highly consistent growth orientation, and can achieve a more regular and compact arrangement when they agglomerate into secondary particles.
[0038] Furthermore, the particle size D50 of the secondary particles is 7μm to 11μm; for example, it can be 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10.0μm, 10.2μm, 10.8μm, 11.0μm, etc. More preferably, the particle size D50 of the secondary particles is 7.5μm to 10μm; for example, it can be 7.5μm, 7.8μm, 8.0μm, 8.3μm, 8.6μm, 8.9μm, 9.2μm, 9.5μm, 9.8μm, 10.0μm, etc.
[0039] Furthermore, the particle size distribution width (Span) of the secondary particles is 0.55~0.9; for example, it can be 0.55, 0.60, 0.65, 0.70, 0.75, 0.78, 0.82, 0.85, 0.88, 0.90, etc. More preferably, the particle size distribution width (Span) of the secondary particles is 0.60~0.70; for example, it can be 0.60, 0.61, 0.62, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, etc.
[0040] The moderate median particle size and concentrated particle size distribution not only ensure that the precursor powder has excellent flowability, but also provide excellent particle size distribution for the subsequent preparation of cathode materials into electrodes. This helps to achieve highly dense packing between particles in the rolling process, thereby significantly improving the compaction density of the electrode and the volumetric energy density of the battery.
[0041] This application provides a method for preparing a phosphorus-doped lithium-rich manganese-based hydroxide precursor as described above. This method is mainly based on co-precipitation technology, achieving uniform bulk doping of phosphate ions within the precursor lattice and densification reconstruction of the particle morphology through precise chemical source selection and multidimensional reaction kinetic control. Specifically, the method includes: Step S1: A mixed salt solution containing nickel metal salt and manganese metal salt, an alkaline solution, and a phosphorus source solution are simultaneously and concurrently injected into a reaction vessel containing a base liquid to carry out a co-precipitation reaction; wherein the solute in the phosphorus source solution is sodium phosphate dodecahydrate.
[0042] In this step, after the reaction system has stabilized in a reaction vessel pre-containing a base solution (for establishing the initial fluid environment), a mixed salt solution containing nickel and manganese metal salts, an alkaline solution for adjusting the precipitation environment, and a specific phosphorus source solution are simultaneously and concurrently injected through a feeding system to initiate a co-precipitation reaction. This simultaneous and concurrent feeding method ensures that the local ion concentration and supersaturation within the system remain relatively stable, allowing phosphorus to uniformly penetrate and distribute within the continuously growing precursor particles along with the precipitation process of the metal hydroxides, rather than merely accumulating on the particle surface.
[0043] In this embodiment, the solute in the phosphorus source solution is specifically selected as sodium phosphate dodecahydrate. Sodium phosphate dodecahydrate can completely dissociate into free phosphate ions (PO4) in aqueous solution. 3- ) and sodium ions (Na + In this process, phosphate ions can directly participate in co-precipitation and replace some hydroxide ions into the crystal lattice without undergoing complex valence state transformations; while the coexisting sodium ions have extremely high water solubility and can be completely removed in subsequent washing processes. This special phosphorus source not only ensures the purity of bulk doping and avoids the problem of impurity residue caused by the introduction of ammonium ions or complex hydrogen phosphate ions, but also meets the environmental and economic requirements of large-scale industrial production due to its low cost and absence of complex waste emissions.
[0044] In step S2, during the coprecipitation reaction, gas is introduced into the reaction vessel, and as the reaction proceeds, the feed flow rates of the mixed salt solution and the phosphorus source solution, the stirring speed in the reaction vessel, and the gas flow rate are adjusted to obtain the reaction product.
[0045] In this step, as the coprecipitation reaction proceeds, gas is introduced into the reaction vessel, and the feed flow rates of the mixed salt solution and the phosphorus source solution are adjusted in real time to maintain a suitable supersaturation of the reaction and control the nucleation and growth rate of the crystals. At the same time, the stirring speed in the reaction vessel is adjusted to provide matching fluid shear force for particles of different particle sizes, promoting the regular and compact agglomeration of primary particles into secondary particles.
[0046] Furthermore, the gas flow rate is synergistically controlled during the reaction to fine-tune the atmosphere within the reactor. Through the coupled synergistic control of the feed, fluid dynamics, and reaction atmosphere, combined with the crystal plane modification effect of phosphate heteroions, ineffective particle growth along the a-axis can be effectively suppressed, inducing dominant growth along the c-axis. Ultimately, this results in refined primary particle size and consistent orientation, thereby obtaining spherical or near-spherical precursors with extremely high internal density.
[0047] Step S3: After solid-liquid separation, washing and drying, the reaction product is obtained as the phosphorus-doped lithium-rich manganese-based hydroxide precursor.
[0048] After the coprecipitation reaction reaches the preset endpoint, the resulting slurry-like reaction product is removed from the reaction vessel and sequentially undergoes solid-liquid separation (such as centrifugal dehydration), washing (such as water washing to remove residual soluble sodium salts and other impurities), and drying treatment (such as drying and other conventional post-processing processes) to finally obtain the phosphorus-doped lithium-rich manganese-based hydroxide precursor powder product with high purity and high tap density.
[0049] In some embodiments, the step of introducing gas into the reaction vessel specifically includes increasing the gas flow rate as the reaction time increases during the coprecipitation reaction.
[0050] In some embodiments, the stirring speed in the reaction vessel is reduced as the particle size of the precursor in the reaction system increases.
[0051] In the coprecipitation reaction, embodiments of the present invention employ a dynamic fluid dynamics and aerodynamics control strategy. On one hand, the stirring speed within the reaction vessel is reduced as the precursor particle size increases in the reaction system. In the initial stage of the reaction, a higher stirring speed provides sufficient shear force to prevent abnormal agglomeration of fine particles; as the particles grow, reducing the stirring speed effectively reduces mechanical collisions and wear between particles, protecting the spherical structure of secondary particles and promoting the dense packing of primary particles.
[0052] On the other hand, during the coprecipitation reaction, the gas flow rate is increased as the reaction time increases. This gradual increase in gas flow with increasing reaction time avoids excessive oxidation of small particles in the early stages of the reaction. In the later stages of particle growth, the increased gas flow rate can synergistically work with the adsorption-induced effect of phosphate ions in the system to maintain the dominant growth of crystals along a specific crystal orientation (such as the c-axis), thereby achieving precise control over the internal density of the precursor.
[0053] In some embodiments, prior to the coprecipitation reaction, a step of preparing the base solution is included: injecting a mixed salt solution containing nickel metal salt and manganese metal salt, along with an alkaline solution, into a reaction vessel to carry out nucleation and growth reactions; after separation to obtain seed crystals, the seed crystals are mixed with water to obtain the base solution.
[0054] Specifically, a mixed salt solution containing nickel and manganese metal salts, along with an alkaline solution, is injected into a reaction vessel. Rapid nucleation and initial growth reactions occur under high supersaturation. Uniform seed crystals are then obtained through conventional separation methods such as centrifugation and filtration. Subsequently, the pre-prepared seed crystals are mixed with water (such as deionized water) and slurried to obtain the base solution used in the main reaction. By isolating nucleation and growth in time and space or at different stages, in the subsequent co-precipitation main reaction, metal ions and phosphate groups will primarily rely on the surface of the existing seed crystals for epitaxial growth, effectively suppressing secondary spontaneous nucleation within the system. This mechanism significantly narrows the particle size distribution of the final precursor product, ensuring high uniformity in particle size.
[0055] In some embodiments, during the coprecipitation reaction, the pH of the reaction system within the reaction vessel is controlled between 9.00 and 9.60. For example, the pH values can be 9.00, 9.05, 9.10, 9.20, 9.30, 9.35, 9.40, 9.45, 9.50, 9.60, etc.
[0056] This weakly alkaline environment provides optimal thermodynamic and kinetic equilibrium conditions for the co-precipitation of nickel and manganese ions and the lattice substitution of phosphate, ensuring that the precursor product has a pure phase structure and excellent electrochemical activity.
[0057] In embodiments of the present invention, the stirring speed within the reaction vessel is reduced as the precursor particle size increases within the reaction system. Specifically, to achieve precise matching between reaction kinetics and precursor particle growth state, this application employs a multi-stage dynamic coupling control strategy. Based on the monitored real-time precursor particle size, the feed flow rate, pH value, and stirring speed are continuously and systematically regulated in a stepwise manner, specifically including the following multiple consecutive growth stages: The first stage involves simultaneously injecting the mixed salt solution, the alkaline solution, and the phosphorus source solution at initial flow rates, while adjusting the flow rate of the alkaline solution to maintain the pH of the reaction system between 9.00 and 9.20. For example, the pH value in the first stage can be 9.00, 9.02, 9.05, 9.08, 9.10, 9.12, 9.15, 9.18, 9.20, etc. In the initial stage of the reaction, the precursor particles are small in size and have high surface energy. Maintaining a relatively high initial stirring speed provides sufficient fluid shear force to effectively break up soft agglomerates and prevent abnormal aggregation of small particles. Simultaneously, the relatively small initial flow rate matches the small total surface area of the particles at this stage, avoiding secondary nucleation caused by excessive local supersaturation.
[0058] The second stage involves increasing the feed flow rates of the mixed salt solution and the phosphorus source solution to 1.8 to 2.2 times the initial flow rates. For example, the feed flow rates can be increased to 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, etc., of the initial flow rates. The pH of the reaction system is controlled to be maintained between 9.20 and 9.40. For example, the pH value can be 9.20, 9.22, 9.25, 9.28, 9.30, 9.32, or 9.30. 5, 9.38, 9.40, etc.; when the particle size $D_{50}$ of the precursor in the system is monitored to reach 30%~35% of the target total particle size (for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, etc.), the linear velocity of the stirring speed is reduced to 7.0~7.5 m / s. For example, the linear velocity of the stirring speed can be 7.0 m / s, 7.1 m / s, 7.2 m / s, 7.25 m / s, 7.3 m / s, 7.4 m / s, 7.45 m / s, 7.5 m / s, etc.
[0059] Third stage: As the particles grow further, the feed flow rate is increased to 2.8 to 3.2 times the initial flow rate, for example, it can be 2.8 times, 2.85 times, 2.9 times, 2.95 times, 3.0 times, 3.05 times, 3.1 times, 3.15 times, 3.2 times, etc.; the pH of the reaction system is controlled to be maintained between 9.40 and 9.60, for example, the pH value can be 9.40, 9.42, 9.45, 9.48, 9.50, 9.52, 9.55, 9.58. 9.60, etc.; when the particle size D50 of the precursor in the system reaches 48%~55% of the target total particle size (for example, it can be 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, etc.), the linear velocity of the stirring speed is further reduced to 6.0~6.5 m / s, for example, it can be 6.0 m / s, 6.1 m / s, 6.17 m / s, 6.2 m / s, 6.3 m / s, 6.4 m / s, 6.45 m / s, 6.5 m / s, etc.
[0060] Fourth stage: Increase the feed flow rate to 3.8 to 4.2 times the initial flow rate, for example, 3.8 times, 3.85 times, 3.9 times, 3.95 times, 4.0 times, 4.05 times, 4.1 times, 4.15 times, 4.2 times, etc.; control the pH of the reaction system to be maintained between 9.20 and 9.40; when the particle size D50 of the precursor in the system reaches 60% to 68% of the target total particle size (for example, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, etc.), reduce the linear velocity of the stirring speed to 5.0 to 5.5 m / s, for example, 5.0 m / s, 5.1 m / s, 5.14 m / s, 5.2 m / s, 5.3 m / s, 5.4 m / s, 5.45 m / s, 5.5 m / s, etc.
[0061] The aforementioned multi-stage synergistic regulation mechanism lies in the fact that, as the reaction continues, the total surface area of the precipitate in the system increases geometrically. The stepped increase in feed flow rate can dynamically compensate for the reactant consumption caused by the increase in surface area, maintaining a constant and suitable supersaturation in the reaction system, ensuring that phosphate and metal ions continuously and uniformly co-precipitate into the crystal lattice. At the same time, by monitoring the particle size D50 in real time, the stirring speed is adjusted in a timely manner at specific stages of particle growth, effectively reducing the mechanical collision and severe wear between large particles in the fluid, protecting the spherical structure of secondary particles from damage from a hydrodynamic perspective, and avoiding the generation of micropowder. Combined with the finely adjusted pH environment at each stage, it ultimately promotes the close arrangement of primary particles, significantly improving the internal density and overall tap density of the precursor.
[0062] In some embodiments, this application employs a dynamic aerodynamic control strategy for the atmospheric environment during the coprecipitation reaction, which involves gradually increasing the flow rate of the oxidizing gas as the reaction time increases. Specifically, during the coprecipitation reaction, increasing the gas flow rate as the reaction time increases includes: After injecting the mixed salt solution, the alkaline solution, and the phosphorus source solution for 2.5 to 3.5 hours (e.g., 2.5 hours, 2.6 hours, 2.8 hours, 3.0 hours, 3.2 hours, 3.4 hours, 3.5 hours, etc.), the gas is introduced into the reaction vessel at an initial flow rate. In the initial stage of the coprecipitation reaction, the precursor particles are small in size and have high surface activity. This delayed aeration method can effectively avoid excessive oxidation of the small particles in the early stage of the reaction and protect the stable formation of the initial crystal lattice.
[0063] Furthermore, in order to match the kinetic requirements of particle growth, the initial flow rate is controlled at a low level, namely 0.05 L / h to 0.15 L / h; for example, it can be 0.05 L / h, 0.06 L / h, 0.08 L / h, 0.10 L / h, 0.12 L / h, 0.14 L / h, 0.15 L / h, etc.
[0064] After that, the gas flow rate is increased every 2.5 to 3.5 hours until the gas flow rate reaches the preset maximum flow rate threshold.
[0065] Furthermore, the gas flow rate can be increased by 0.15 L / hour to 0.25 L / hour each time; for example, it can be 0.15 L / hour, 0.16 L / hour, 0.18 L / hour, 0.20 L / hour, 0.22 L / hour, 0.24 L / hour, 0.25 L / hour, etc. Furthermore, the preset maximum flow rate threshold is 1.8 L / hour to 2.0 L / hour. For example, it can be 1.8 L / hour, 1.85 L / hour, 1.9 L / hour, 1.95 L / hour, 2.0 L / hour, etc.
[0066] In the mid-to-late stages of particle growth, the precursor particles increase in size. The gradually increasing gas flow rate not only provides a mild and continuous oxidizing environment to match the particle size increase, but also has a synergistic effect with the adsorption-induced effect of phosphate in the system. The moderate oxidizing atmosphere, combined with the modification of crystal facet energy by phosphate as a heterogeneous ion, maintains and guides the dominant growth of crystals along specific crystal orientations (such as the c-axis), thereby achieving precise control over the internal density of the precursor and significantly improving the compaction density of the particles.
[0067] In some embodiments, the gas introduced into the reaction vessel is air, oxygen, or a mixture of oxygen and an inert gas.
[0068] In some embodiments, the preparation step of the base liquid further includes: introducing air, oxygen, or a mixture of oxygen and an inert gas (such as nitrogen or argon) into the reaction vessel.
[0069] This atmosphere switching mechanism ensures the high purity and uniformity of the initial seed crystal composition by providing an absolutely oxygen-free inert environment during the nucleation stage, laying the foundation for the densification and epitaxial growth of particles in the subsequent main coprecipitation reaction.
[0070] This application provides a lithium-rich manganese-based cathode material. It is prepared by mixing a phosphorus-doped lithium-rich manganese-based hydroxide precursor as described above, or a phosphorus-doped lithium-rich manganese-based hydroxide precursor prepared by the method described above, with a lithium source and then sintering.
[0071] This cathode material uses a high-density phosphorus-doped lithium-rich manganese-based hydroxide precursor obtained by the aforementioned preparation method as the matrix material. This precursor is thoroughly mixed with a lithium source and then prepared via a high-temperature solid-state sintering reaction. The lithium source can be a conventional lithium-containing compound, such as lithium carbonate, lithium hydroxide, or lithium nitrate. The mixing method can employ mechanical high-energy ball milling or a high-speed mixer to ensure uniform mixing. During the high-temperature sintering stage, lithium ions are extensively embedded in the transition metal layered framework of the precursor, achieving a transformation to a lithium-rich oxide phase. Benefiting from the densely arranged microscopic primary particles and extremely low internal porosity within the precursor, the resulting cathode material inherits excellent macroscopic physical morphology. This lays the material foundation for achieving high solid density of the electrode in subsequent battery manufacturing processes, which is beneficial for significantly increasing the volumetric energy density of lithium-ion batteries.
[0072] Furthermore, the surface of the lithium-rich manganese-based cathode material has an in-situ derived amorphous Li3PO4 coating layer. Because the precursor introduces bulk doping of phosphate anions during the co-precipitation stage, during the high-temperature sintering and lithium formulation process, the doped phosphate ions react in-situ with the residual or enriched lithium salts in the mixed system on the particle surface, spontaneously generating a uniform and dense amorphous Li3PO4 layer. Compared to traditional external coating processes, this "in-situ derived" coating method results in a stronger interfacial bond, higher coating uniformity, and less flaking.
[0073] The in-situ derived amorphous Li3PO4 coating endows the cathode material with excellent interfacial stability. Amorphous Li3PO4, as an excellent fast-ion conductor, ensures rapid lithium-ion transport at the solid-liquid interface and reduces charge transfer resistance while acting as a robust chemical barrier. It effectively blocks direct physical contact between the highly active electrode surface and the electrolyte, greatly suppresses oxidation side reactions at the interface, and blocks the dissolution channels of transition metal ions such as manganese at the source. Through the synergistic effect of the optimized bulk structure and in-situ interface protection, the cathode material provided in this embodiment significantly improves the technical bottlenecks of layered lithium-rich manganese-based materials, such as severe voltage decay and structural collapse during long-term charge-discharge cycles, exhibiting good cycle stability and high-rate charge-discharge performance.
[0074] From a chemical thermodynamics perspective, during the high-temperature solid-state sintering process of lithium formulation, the reaction of phosphate ions enriched on the surface and near-surface of precursor particles with molten lithium salt to form Li3PO4 is spontaneous and possesses extremely high reaction driving force. Subsequent electrochemical test results (such as the significant suppression of voltage decay during high-temperature cycling) also conclusively confirm, from a macroscopic performance perspective, the existence of this amorphous interface protective layer and its excellent effect in resisting side reactions.
[0075] In some embodiments of this application, a lithium-ion battery is provided. The core energy storage component of this lithium-ion battery includes a positive electrode, the active material of which is a lithium-rich manganese-based positive electrode material with high density and high interfacial stability prepared as described above. In addition to the positive electrode, the lithium-ion battery typically includes conventional components such as a negative electrode, a separator, an electrolyte, and a battery casing. The negative electrode active material can be a carbon-based material (such as natural graphite or artificial graphite), a silicon-based material, or lithium titanate; the separator can be a polyolefin microporous membrane such as polypropylene or polyethylene; the electrolyte typically contains a non-aqueous organic solvent and lithium salt dissolved therein. Thanks to the excellent physical density of the positive electrode material and the in-situ derived surface and interfacial protection structure, this lithium-ion battery not only exhibits excellent volumetric energy density but also effectively resists voltage decay during long-cycle charge-discharge cycles, demonstrating superior electrochemical performance. Depending on the shape and packaging process, the specific type of the lithium-ion battery may include, but is not limited to, cylindrical batteries, prismatic batteries, pouch batteries, or button batteries; depending on the application field, the lithium-ion battery may include, but is not limited to, power batteries, energy storage batteries, or consumer (3C) digital batteries.
[0076] In some other embodiments of this application, an electrical device is provided. This device uses the aforementioned lithium-ion battery as its primary power source or energy storage unit. Due to the high energy density and extremely long cycle life of the built-in lithium-ion battery, the device's range or standby time after a single charge can be significantly improved, and the degradation rate and replacement / maintenance costs of the battery module throughout the device's lifespan can be greatly reduced. The electrical device encompasses all types of terminal electronic and electromechanical products that rely on electric power or have energy storage requirements. Specific types may include, but are not limited to: new energy vehicles (such as pure electric vehicles, plug-in hybrid electric vehicles, and hybrid electric vehicles), light electric vehicles (such as electric bicycles, electric motorcycles, and electric balance scooters), consumer portable electronic products (such as smartphones, tablets, laptops, smart wearable devices, and drones), power tools (such as electric drills and electric lawnmowers), and various industrial, commercial, or residential energy storage system equipment.
[0077] The present application is further illustrated below with specific embodiments. However, it should be understood that these embodiments are merely for the purpose of more detailed illustration and should not be construed as limiting the present application in any way.
[0078] Example 1 This embodiment provides a phosphorus-doped lithium-rich manganese-based hydroxide precursor.
[0079] Experimental methods: (1) Material preparation: Prepare a mixed salt solution containing nickel sulfate and manganese sulfate at a molar ratio of 45:55 for nickel and manganese metal ions. The total molar concentration of metal ions in the mixed salt solution is 2 mol / L. Prepare a 10 mol / L sodium hydroxide solution. Prepare a 0.274 mol / L sodium phosphate dodecahydrate (Na3PO4) solution. A 12H2O solution was used as the phosphorus source solution.
[0080] (2) Seed preparation: 100L of pure water and sodium hydroxide solution were added to a 300L reactor as the first base liquid. The linear velocity of the stirring speed was adjusted to 8.00m / s, the reactor temperature was controlled at 65℃, and the pH value was adjusted to 11.63 with sodium hydroxide solution. At the same time, nitrogen protective gas (flow rate 8L / min) was continuously introduced into the reactor for 4 hours. After the system stabilized, the nucleation reaction was carried out for 0~20 minutes: the mixed salt solution flow rate was 7.2L / h, the sodium hydroxide solution flow rate was 2.6L / h, and the sodium dodecahydrate phosphate solution flow rate was 0.3mL / min, which were fed in parallel to maintain the pH of the reaction system between 11.60 and 11.70. After the nucleation was completed, the growth stage was entered: the flow rate of the mixed salt solution was adjusted to 21.6L / h and the flow rate of the sodium dodecahydrate phosphate solution was 0.8mL / min, and the pH of the reaction system was reduced to between 10.00 and 10.20. The reaction was stopped when the precursor particle size D50 reached 2.30 μm. The slurry was washed with water (80℃, 60~120 minutes) and centrifuged to dry to 40~50% moisture content to obtain seed crystals for later use.
[0081] (3) Co-precipitation growth: 100L of pure water and 6kg (dry basis) of the above-mentioned seed crystals were added to a 300L reactor to form a second base solution. The stirring speed and linear velocity were adjusted to 8.00m / s, the temperature was 45℃, and nitrogen protective gas (flow rate 20L / min) was continuously introduced for 4 hours. After the system stabilized, a mixed salt solution, sodium hydroxide solution, and sodium dodecahydrate solution were injected simultaneously and in parallel, and the following stages were followed: 1) First stage: Inject the mixed salt solution at a flow rate of 7.2 L / h and the sodium dodecahydrate solution at a flow rate of 0.8 mL / min, and control the pH to be maintained between 9.00 and 9.20; 2) Second stage: Increase the flow rate of the mixed salt solution to 14.4 L / h and the flow rate of the sodium dodecahydrate phosphate solution to 1.6 mL / min, and control the pH to be maintained between 9.20 and 9.40; when the precursor particle size D50 reaches 30% to 35% of the total particle size, the rotation speed is gradually reduced to 7.20 m / s. 3) Third stage: Increase the flow rate of the mixed salt solution to 21.6 L / h and the flow rate of the sodium dodecahydrate phosphate solution to 2.4 mL / min, and control the pH to be maintained between 9.40 and 9.60; after the precursor particle size D50 reaches 48% to 55% of the total particle size, reduce the rotation speed to 6.17 m / s; 4) Fourth stage: Increase the flow rate of the mixed salt solution to 28.8 L / h and the flow rate of the sodium dodecahydrate phosphate solution to 3.1 mL / min, and control the pH to be maintained between 9.20 and 9.40; after the precursor particle size D50 reaches 60% to 68% of the total particle size, reduce the rotation speed to 5.14 m / s.
[0082] Three hours after feeding, the air source was switched to air, with the initial air flow rate set at 0.1L / hour; thereafter, the air flow rate was increased by 0.2L / hour every 3 hours until it reached 1.9L / hour.
[0083] (4) Post-processing: Feeding was stopped after the D50 of the reaction product reached 7.52 μm. The slurry was aged, washed, dried and sieved to obtain Ni. 0.45 Mn 0.55 (OH)2 3x (PO4) x The precursor product, where x≈0.0003, corresponds to a phosphorus element mass fraction of 100ppm.
[0084] Example 2 This embodiment provides a phosphorus-doped lithium-rich manganese-based hydroxide precursor.
[0085] The preparation method in this embodiment is basically the same as that in Example 1, except that the molar ratio of nickel to manganese in the mixed salt solution is adjusted to 40:60; during the S2 growth stage, the flow rates of the sodium dodecahydrate phosphate solution in the first to fourth stages are adjusted to 1.3 mL / min, 2.6 mL / min, 3.9 mL / min, and 5.2 mL / min, respectively; air is introduced 2 hours after feeding, with an initial flow rate of 0.2 L / h, which is then increased by 0.2 L / h every 3 hours until reaching 2.4 L / h; the process is stopped when the product D50 reaches 7.68 μm. The precursor product obtained has x≈0.0010, corresponding to a phosphorus mass fraction of 350 ppm.
[0086] Example 3 This embodiment provides a phosphorus-doped lithium-rich manganese-based hydroxide precursor.
[0087] The preparation method in this embodiment is basically the same as that in Example 1, except that: the molar ratio of nickel to manganese in the mixed salt solution is adjusted to 50:50; during the S2 growth stage, the flow rates of the sodium dodecahydrate phosphate solution in the first to fourth stages are adjusted to 1.8 mL / min, 3.7 mL / min, 5.5 mL / min, and 7.3 mL / min, respectively; air is introduced immediately after feeding, with an initial flow rate of 0.3 L / h, which is then increased by 0.2 L / h every 2 hours until reaching 2.3 L / h; the process is stopped when the product D50 reaches 9.82 μm. The precursor product Ni is obtained. 0.50 Mn 0.50 (OH) 2-3x (PO4) x In the figure, x≈0.0015 corresponds to a phosphorus mass fraction of 500ppm.
[0088] Comparative Example 1 This comparative example provides a pure-phase carbonate-rich manganese-based hydroxide precursor as a blank control to investigate the effect of no phosphorus doping on the morphology and properties of the precursor particles.
[0089] The preparation method of this comparative example is basically the same as that of Example 1, except that sodium phosphate dodecahydrate solution is not used as a phosphorus source. In the specific steps, the nickel-manganese ratio is 35:65. No phosphorus source is added in the nucleation and growth stages of S1, and the pH is controlled at 11.70~11.80 and 10.20~10.40, respectively; the volume of the seed crystal reaction liquid is 120L, the rotation speed is 8.10m / s, and the temperature is 45℃. No phosphorus source is added in the growth stage of S2. The feed flow rate of the metal salt in the first to fourth stages is the same as that in Example 1, and the pH is controlled at 9.40~9.50, 9.30~9.40, 9.20~9.30, and 9.00~9.20, respectively. When the D50 reaches 50%~60%, 60%~68%, and 80%~86% of the total particle size, the feed rate is reduced to 6.50m / s, 5.17m / s, and 4.14m / s, respectively. After feeding for 1 hour, air was introduced (0.1 L / h, increasing by 0.2 L / h every 5 hours to 1.5 L / h). The process was stopped when the product D50 reached 9.81 μm. Undoped pure-phase Ni was obtained. 0.35 Mn 0.65 (OH)2 precursor.
[0090] Comparative Example 2 This comparative example provides a lithium-rich manganese-based precursor with excessive phosphorus doping, mainly used to investigate the negative impact of overdoping caused by excessive phosphorus doping (1200 ppm) on particle morphology.
[0091] The difference between this comparative example and Example 1 lies in the significantly increased phosphorus source feed rate: the flow rates of the sodium dodecahydrate phosphate solution in the first to fourth stages were adjusted to 4.2, 8.3, 12.5, and 16.6 mL / min, respectively; air was introduced immediately after feeding, initially at 0.5 L / h, increasing by 0.3 L / h every 2 hours to 3.8 L / h; the process was stopped when the product D50 reached 9.96 μm. The resulting precursor product had x≈0.0035, corresponding to a phosphorus element mass fraction as high as 1200 ppm.
[0092] Comparative Example 3 This comparative example provides another comparative example with severe phosphorus overdosing (2000 ppm). The difference from Example 1 is that the flow rates of the sodium dodecyl phosphate solution in the first to fourth stages were adjusted to 6.2, 12.5, 18.7, and 24.9 mL / min, respectively; air was introduced immediately after feeding, initially at 0.6 L / h, increasing by 0.4 L / h every 3 hours to 4.2 L / h; the process was stopped when the product D50 reached 7.64 μm. The resulting precursor product had x ≈ 0.0059, corresponding to a phosphorus mass fraction of 2000 ppm.
[0093] Test Experiment Example The morphology and performance of the precursors and cathode materials obtained by the above embodiments and comparative examples and subsequent sintering were observed and tested.
[0094] Experimental Example 1: Microscopic Morphology and Phase Structure Analysis (1) SEM morphology observation: The precursors of Example 1 and Comparative Example 1 and Comparative Example 2 were tested by scanning electron microscopy (SEM).
[0095] refer to Figure 1 (SEM image of the precursor in Example 1) and Figure 4 (SEM image of the undoped precursor in Comparative Example 1) The comparison shows that after introducing an appropriate amount of phosphorus, the primary particles of the precursor in Example 1 are significantly refined, and the macroscopic packing of the secondary particles is more dense. However, due to... Figure 6 (Comparative Example 2, SEM image of the precursor) It can be seen that when the phosphorus doping amount is too high (e.g., 1200 ppm), a significant "overdoping effect" occurs, which causes the primary particles of the precursor to become abnormally coarsened and the aspect ratio to increase significantly.
[0096] (2) Profile and elemental distribution analysis: The SEM image of the profile of Example 1 is shown below. Figure 2 As shown, the cross-sectional phosphorus element EDS surface scan image is as follows. Figure 3 As shown. By Figure 3 The distribution of green signal points indicates that the phosphorus signal is uniformly distributed across the cross-section of the precursor particles, with no surface enrichment or obvious segregation observed. This result demonstrates that the phosphorus added using this method achieves effective bulk doping and is essentially uniformly distributed within the material.
[0097] (3) Crystal structure (XRD) analysis: The precursors of Example 1 and Comparative Example 1 were sintered with lithium source to form cathode materials, and then characterized by XRD. The results are as follows: Figure 5 As shown, both retained the characteristic peaks of the layered α-NaFeO2 structure (space group R3m), indicating that appropriate phosphate bulk doping did not change the overall layered crystal framework structure. However, in Example 1, I... (110) / I (108) The peak intensity ratio (0.71) was significantly lower than that of Comparative Example 1 (0.84), which is attributed to the effective suppression of the growth of the {010} active surface by phosphate doping. In addition, the (003) peak of Example 1 showed a slight shift to a lower angle, indicating that the larger radius of phosphate doping increased the lattice constant of the c-axis, which thermodynamically promoted the diffusion of lithium ions during subsequent charge and discharge processes.
[0098] Furthermore, due to the introduction of phosphate, the formation of strong PO covalent bonds effectively suppresses the phase transformation of the disordered rock salt phase on the surface of the cathode material, further explaining the underlying reason for the preferred growth orientation of the (003) crystal plane, which provides crystallographic assurance for the structural stability of the material in long-term cycling.
[0099] Experimental Example 2: Testing of Physicochemical Properties of Precursor Powder In this experimental example, the physicochemical parameters of the precursors prepared in each embodiment and comparative example were tested.
[0100] 1. Testing method: (1) Particle size distribution test: The precursor sample was tested using a laser particle size analyzer (Malvin MasterSizer3000) and parameters such as median diameter D50 and particle size distribution width were recorded.
[0101] (2) Element content test: The amount of phosphorus doping in the precursor (mass fraction, ppm) was accurately determined by inductively coupled plasma optical emission spectrometry (ICP-OES).
[0102] (3) Microscopic morphology analysis: The surface and cross-sectional morphology of the precursor were observed using a scanning electron microscope (SEM), and the length and thickness of the primary particles in the SEM image were measured and statistically analyzed at multiple points using Nano Measurer image measurement software.
[0103] (4) Tap density (TD) test: The tap density of the precursor powder was tested using a Dandong Baite BT-310 series tap density meter according to the relevant standard procedures.
[0104] (5) Specific surface area (BET) test: The specific surface area of the precursor powder was determined by low temperature nitrogen adsorption method using an ASAP 2460 specific surface area analyzer from the American Micro Instruments Company, by static volumetric method or dynamic chromatography method.
[0105] 2. Test Results: The results are summarized in Table 1: Table 1. Relevant Product Characteristics of Ternary Precursors
[0106] 3. Analysis: As shown in Table 1, within a reasonable doping range (Examples 1-3, 100~500ppm), the aspect ratio of the primary particles was controlled at 2.33~2.60, and the thickness was refined to 50~62nm. This refinement and uniform orientation significantly improved the physical processing properties of the macroscopic powder: its tap density (TD) reached 1.63~1.72g / cm³, its specific surface area was controlled at 28.21~40.29m² / g, and its particle size distribution span was narrow to 0.60~0.65, demonstrating excellent compactness. In contrast, the undoped Comparative Example 1 had coarse primary particles (aspect ratio 3.64), while the overdoped Comparative Examples 2 and 3 (1200ppm and 2000ppm) exhibited abnormal coarsening due to overdoping. Although their tap density increased in absolute value due to the coarsening of the primary particles, their specific surface area decreased sharply (14.72~18.42m² / g). This collapse of the microstructure is not conducive to the uniform penetration of lithium ions and the construction of the electrochemical interface during subsequent sintering.
[0107] Experiment Example 3: Electrochemical Performance and Cycle Life Testing of Cathode Materials In this experimental example, the performance of the button cell battery was tested.
[0108] 1. Testing method: (1) Preparation of cathode material: The precursor samples prepared in each example and comparative example were taken and uniformly mixed with lithium hydroxide (LiOH·H2O) at a molar ratio of 1:1.10. The mixture was placed in a muffle furnace and sintered at 650℃ for 12 hours under a pure oxygen (O2) atmosphere. After natural cooling, it was crushed and sieved to obtain the corresponding lithium-rich manganese-based cathode material.
[0109] (2) Preparation of positive electrode sheet: The obtained positive electrode material, conductive agent (acetylene black) and binder (PVDF) are mixed in a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added. The mixture is stirred at high speed to prepare a uniform electrode slurry. The slurry is uniformly coated on an aluminum foil current collector, vacuum dried, rolled and compacted, and then punched into circular sheets of a specific size for use as positive electrode sheets.
[0110] (3) Assembly of button cells: In a glove box filled with high-purity argon (water and oxygen content are both less than 1 ppm), the above-mentioned positive electrode sheet is used as the positive electrode, the lithium metal sheet is used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) is used as the separator, and an appropriate amount of liquid electrolyte (prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) with a volume ratio of 1:1) is injected to assemble CR2032 type button cells.
[0111] (4) Electrochemical performance testing: The assembled coin cells were tested for charge and discharge characteristics using the LAND battery testing system at a constant temperature of 25°C. The test conditions were set as follows: constant current charging and discharging at a charge and discharge rate of 0.1C within a voltage range of 2.8V to 4.3V. The first charge and discharge capacity, coulombic efficiency, and voltage decay (voltage drop) data before and after cycling were recorded for each group of cells.
[0112] 2. Test Results: The results are summarized in Table 2 (electrochemical performance) and Table 3 (voltage decay data before and after cycling at 45°C): Table 2. Electrochemical Performance
[0113] Table 3. Voltage decay data before and after 45℃ cycling.
[0114] 3. Analysis: As shown in Table 2, the cathode materials of Examples 1-3 exhibit excellent electrochemical activity, with initial discharge specific capacity of 192.78~203.61 mAh / g at 0.1C, initial charge-discharge efficiency exceeding 91.80%, and capacity retention of 89.80%~91.20% after 100 cycles. In contrast, the discharge capacity of the comparative examples is generally lower, with the worst cycle retention rate dropping to 83.20%.
[0115] Voltage decay is a fatal weakness of lithium-rich materials. As shown in Table 3, after 100 cycles at 45°C, the discharge midpoint voltage of Example 1 only decreased from 3.78V to 3.69V, a cumulative decay of only 0.09V; while the undoped Comparative Example 1 experienced a dramatic drop from 3.75V to 3.42V, a decay of 0.33V. This fully demonstrates that the bulk phosphorus doping of this invention, and the in-situ generation of an amorphous coating layer during sintering, can significantly stabilize the structure, suppress interfacial side reactions, and thus greatly alleviate the voltage decay of the material.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A phosphorus-doped lithium-rich manganese-based hydroxide precursor, characterized in that, The chemical formula of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is Ni. a Mn b (OH) 2-3x (PO4) x ; wherein 0.4≤a≤0.6, 0.4≤b≤0.6, a+b=1, and 0.0001<x≤0.0015; In the phosphorus-doped lithium-rich manganese-based hydroxide precursor, the phosphorus element is doped in the crystal lattice of the precursor in the form of phosphate ions, and replaces part of the hydroxide ions.
2. The phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 1, characterized in that, x satisfies 0.0003<x≤0.0015; and / or, The mass fraction of the phosphorus element in the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 100 ppm to 500 ppm.
3. The phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 1, characterized in that, The specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 22 m². 2 / g~45m 2 / g; preferably, the specific surface area of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 28m². 2 / g~41m 2 / g; and / or, The tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.0 g / cm³. 3 ~2.2g / cm 3 Preferably, the tap density of the phosphorus-doped lithium-rich manganese-based hydroxide precursor is 1.5 g / cm³. 3 ~1.9g / cm 3 .
4. The phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 1, characterized in that, The precursor is spherical or quasi-spherical secondary particles formed by agglomeration of primary particles; Preferably, the primary particles are acicular or flaky; Preferably, the thickness of the primary particles is 50 nm to 150 nm; Preferably, the length of the primary particles is 130 nm to 500 nm; Preferably, the aspect ratio of the primary particles is ≥2; Preferably, the particle size D50 of the secondary particles is 7 μm to 11 μm; more preferably, the particle size D50 of the secondary particles is 7.5 μm to 10 μm; and / or, Preferably, the particle size distribution width Span of the secondary particles is 0.55 to 0.9; more preferably, the particle size distribution width Span of the secondary particles is 0.60 to 0.
70.
5. A method for preparing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in any one of claims 1-4, characterized in that, comprises: into a reaction vessel containing a base solution, synchronously and concurrently injecting a mixed salt solution containing nickel metal salt and manganese metal salt, an alkali solution, and a phosphorus source solution to carry out a coprecipitation reaction; wherein the solute in the phosphorus source solution is sodium phosphate dodecahydrate; During the coprecipitation reaction, gas is introduced into the reaction vessel, and as the reaction proceeds, the feeding flow rates of the mixed salt solution and the phosphorus source solution, the stirring rotation speed in the reaction vessel, and the gas flow rate of the gas are regulated to obtain a reaction product; The reaction product is subjected to solid-liquid separation, washing and drying treatments to obtain the phosphorus-doped lithium-rich manganese-based hydroxide precursor.
6. The method for preparing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 5, characterized in that, The introducing gas into the reaction vessel specifically comprises: during the coprecipitation reaction, as the reaction time extends, increasing the gas flow rate of the gas; and / or, The stirring rotation speed in the reaction vessel is decreased as the particle size of the precursor in the reaction system increases; and / or, Before the coprecipitation reaction, the method further comprises the step of preparing the base solution: injecting a mixed salt solution containing nickel metal salt and manganese metal salt and an alkali solution into the reaction vessel to carry out nucleation reaction and growth reaction, separating to obtain crystal seeds, and mixing the crystal seeds with water to obtain the base solution; and / or, During the coprecipitation reaction, the pH of the reaction system in the reaction vessel is controlled to be 9.00 to 9.
60.
7. The method for preparing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 6, characterized in that, The step that the stirring rotation speed in the reaction vessel is decreased as the particle size of the precursor in the reaction system increases comprises: First stage: synchronously injecting the mixed salt solution, the alkali solution and the phosphorus source solution at initial flow rates, and adjusting the flow rate of the alkali solution to control the pH of the reaction system to be maintained between 9.00 and 9.20; Second stage: Increase the feed flow rate of the mixed salt solution and the phosphorus source solution to 1.8 to 2.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.20 and 9.40; when the particle size D50 of the precursor in the system reaches 30% to 35% of the target total particle size, reduce the linear velocity of the stirring speed to 7.0 to 7.5 m / s; Third stage: Increase the feed flow rate to 2.8 to 3.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.40 and 9.60; when the particle size D50 of the precursor in the system reaches 48% to 55% of the target total particle size, reduce the linear velocity of the stirring speed to 6.0 m / s to 6.5 m / s. Fourth stage: Increase the feed flow rate to 3.8 to 4.2 times the initial flow rate, and control the pH of the reaction system to be maintained between 9.20 and 9.40; when the particle size D50 of the precursor in the system reaches 60% to 68% of the target total particle size, reduce the linear velocity of the stirring speed to 5.0 to 5.5 m / s.
8. The method for preparing the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in claim 6, characterized in that, During the coprecipitation reaction, as the reaction time increases, the gas flow rate is increased, including: After injecting the mixed salt solution, the alkaline solution, and the phosphorus source solution for 2.5 to 3.5 hours, gas is introduced into the reaction vessel at an initial flow rate. Thereafter, the gas flow rate is increased every 2.5 to 3.5 hours until a preset maximum flow rate threshold is reached. Preferably, the initial flow rate is 0.05 L / hour to 0.15 L / hour; preferably, the increase in gas flow rate each time is 0.15 L / hour to 0.25 L / hour; preferably, the preset maximum flow rate threshold is 1.8 L / hour to 2.0 L / hour; and / or, The gas introduced into the reaction vessel is air, oxygen, or a mixture of oxygen and an inert gas; and / or, The preparation step of the base liquid further includes: introducing air, oxygen, or a mixture of oxygen and an inert gas into the reaction vessel.
9. A lithium-rich manganese-based cathode material, characterized in that, The precursor is prepared by mixing it with a lithium source and then sintering it, using the phosphorus-doped lithium-rich manganese-based hydroxide precursor as described in any one of claims 1-4, or the phosphorus-doped lithium-rich manganese-based hydroxide precursor prepared by the method described in any one of claims 5-8. Preferably, the surface of the lithium-rich manganese-based cathode material has an in-situ derived amorphous Li3PO4 coating layer.
10. A lithium-ion battery, characterized in that, It includes a positive electrode, wherein the active material of the positive electrode includes the lithium-rich manganese-based positive electrode material as described in claim 9.
